Preferensi Bermukim Tenaga Kerja Kawasan Industri Makassar - Herman, Herman; Manaf, Asnawi (JURNAL PEMBANGUNAN WILAYAH & KOTA, 2016)
The consequences of population growth is the increasing housing needs of the community. Labor is part of the low and middle-income people should get the attention of government and developers to meet the housing needs. Problems of housing and settlements can not be regarded as a functional and purely physical problems, but more complex as the problems related to the dimensions of social life that includes social, economic, cultural, ecological, technological and political. Provision of occupancy against labor by governments or developers should consider the desire and tendency to settle labor based on its characteristics as a prospective occupant so as to create housing that is accommodative to the occupants. Preferences settled labor of Makassar Industrial Estate is divided into four categories, which are not thinking of moving their homes, thinking of moving residential, residential moving plan and is ready to move occupancy. Based on the study of labor industrial area of Makassar, obtained results indicate that there are 59% of the workforce did not think to move dwelling occupied at the moment. 32% of its workforce started thinking to relocate occupancy but do not know the right time to move on, 7% of its workforce is planning to move the occupancy by a predetermined time and 2% of the workforce that is ready to move current occupancy. Socio-economic characteristics, housing and residential environment that significantly affect labor preference settled industrial area of Makassar is marital status, type of occupancy, status of ownership and residential neighborhood tranquility.